1998
DOI: 10.1111/j.1440-1746.1998.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori infection on gastric mucosal phospholipid contents and their fatty acid composition

Abstract: To investigate the effect of Helicobacter pylori infection on the 'gastric mucosal barrier', phospholipid contents and the fatty acid composition of endoscopic biopsy specimens of the gastric mucosa were analysed in healthy volunteers with and without H. pylori infection. The gastric corporeal phosphatidylcholine (PC) content of H. pylori-positive healthy volunteers was less than that of H. pylori-negative healthy volunteers (P < 0.05). Moreover, H. pylori-positive healthy volunteers had a decrease in linoleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
8
2
Order By: Relevance
“…Nardone et al have reported that H. pylori infection does not significantly affect fatty acid composition of phospholipids in the gastric biopsy specimens from patients with non‐alcoholic liver cirrhosis 30 . However, in our previous study, 11 H. pylori infection markedly decreased linoleic acid composition and increased arachidonic acid composition of gastric mucosal PC. The reasons for the discrepancies are currently unclear.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Nardone et al have reported that H. pylori infection does not significantly affect fatty acid composition of phospholipids in the gastric biopsy specimens from patients with non‐alcoholic liver cirrhosis 30 . However, in our previous study, 11 H. pylori infection markedly decreased linoleic acid composition and increased arachidonic acid composition of gastric mucosal PC. The reasons for the discrepancies are currently unclear.…”
Section: Discussioncontrasting
confidence: 64%
“…The samples stored were then scraped in 1.5 mL PBS, and then homogenized. Phospholipid determination and fatty acid analysis were performed as previously described 11 . Briefly, total lipids of the whole cell were extracted according to the method of Bligh and Dyer 21 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that colonization of H pylori in the gastric mucosa induces a dramatic change in gastric mucosal phospholipid composition and elevates the metabolites of various eicosanoids from epithelial membrane phospholipid, which has been related to inflammatory host responses in infected gastric environment [5,6]. These causal relationships were further proved by the fact that the eradication of H pylori reduces eicosanoid synthesis, resulting in the normalization of gastric mucosal phospholipid contents and its fatty acid composition [7,8].…”
Section: Abstract Helicobacter Pylori Red Ginseng 5(s)-hete 5-lmentioning
confidence: 99%
“…tients may play a crucial role in H. pylori infection (4). In gastrointestinal epithelia, PGE 2 is implicated in maintaining the normal function and structure of the gastric mucosa by modulating diverse cellular functions such as secretion of fluid and electrolytes, mucosal blood flow, and cell proliferation (5,6).…”
mentioning
confidence: 99%